(untitled) (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2026)
The rapid digital transformation of financial services has significantly increased the volume, velocity, and complexity of financial transactions, creating new opportunities for cybercriminals and fraudsters. Traditional security mechanisms often struggle to detect sophisticated fraud patterns in real time due to limitations in scalability, adaptability, and processing capabilities. Intelligent cloud-native security frameworks have emerged as a transformative solution by integrating cloud computing, artificial intelligence, machine learning, big data analytics, and automated security orchestration into a unified architecture. These frameworks enable continuous monitoring, predictive threat intelligence, real-time anomaly detection, and adaptive response mechanisms that enhance cyber resilience and organizational risk management. Cloud-native technologies provide elasticity, microservices-based deployment, containerized security controls, and distributed processing capabilities that support high-performance fraud detection across dynamic financial environments. Furthermore, intelligent analytics facilitate proactive identification of suspicious transactions, behavioral anomalies, and emerging cyber threats before they cause significant financial losses. This study examines the role of intelligent cloud-native security frameworks in strengthening real-time financial fraud detection, improving cyber resilience, and supporting enterprise-wide risk management. The research explores technological foundations, implementation strategies, security benefits, operational challenges, and future directions. The findings demonstrate that integrating intelligent cloud-native architectures with advanced cybersecurity practices can significantly improve fraud prevention, regulatory compliance, business continuity, and overall financial system security.